Psikoedukasi Pengaruh Zat Nikotin Dalam Rokok Terhadap Kemampuan Belajar Siswa SMP Negeri 1 Dewantara - Maya Lestari; Anis En Nabiilah; Aisyah Herlini; Syanda Munaiya (CV Abid Abadi Jaya, 2025)
Abstract Smoking among teenagers in Indonesia has significantly increased, affecting the quality of Human Resources and academic achievements. This study examines the influence of nicotine in cigarettes on the learning ability of students at SMP Negeri 1 Dewantara through psychoeducational methods. Psychoeducation was conducted to enhance students' understanding of the negative impacts of nicotine, which can cause cognitive disturbances, memory decline, and difficulty concentrating. The results of the community service show that many students are aware of the dangers of smoking, but they lack understanding of the mechanisms of its harm. The results of this activity aim to provide in-depth information and encourage a positive attitude towards health, and it is expected to be applied in daily life to improve their quality of life so that students can avoid the dangers of smoking and have a healthy lifestyle. In addition, this activity is also expected to reduce the number of smokers among teenagers. Through the education provided, it is hoped that students can understand the importance of maintaining health. Keywords: Psychoeducation, smoking, learning ability, health, effects of smoking, adolescents. Abstrak Merokok di kalangan remaja di Indonesia mengalami peningkatan signifikan, memengaruhi kualitas Sumber Daya Manusia (SDM) dan prestasi akademik. Pengabdian menginformasikan pengaruh zat nikotin dalam rokok terhadap kemampuan belajar siswa di SMP Negeri 1 Dewantara melalui metode psikoedukasi. Psikoedukasi dilakukan untuk meningkatkan pemahaman siswa mengenai dampak negatif nikotin, yang dapat menyebabkan gangguan kognitif, penurunan daya ingat, dan kesulitan berkonsentrasi. Hasil pengabdian menunjukkan bahwa banyak siswa menyadari bahaya rokok, tetapi kurang memahami mekanisme kerusakannya. Hasil kegiatan ini bertujuan memberikan informasi yang mendalam dan mendorong sikap positif terhadap kesehatan, serta diharapkan dapat diterapkan dalam kehidupan sehari-hari untuk meningkatkan kualitas hidup mereka agar siswa dapat terhindar dari bahaya rokok dan memiliki pola hidup sehat. Selain itu, kegiatan ini juga diharapkan dapat mengurangi angka perokok di kalangan remaja. Melalui edukasi yang diberikan, diharapkan siswa dapat memahami pentingnya menjaga kesehatan. Keywords: Psikoedukasi, rokok, kemampuan belajar, kesehatan, dampak merokok, remaja.